Preoperative Chemoradiotherapy Versus Postoperative Chemoradiotherapy for Patients With Locally Advanced Gastric Cancer: A Retrospective Study Based on Propensity Score Analyses - Yang, Wang; Zhou, Menglong; Li, Guichao; Shen, Lijun; Wang, Yan; Zhang, Hui; Wang, Yaqi; Zhang, Jing; Sun, Xiaoyang; Zhang, Zhiyuan; Zou, Wei; Zhang, Zhen (Frontiers in Oncology, 2020)
Purpose Although adjuvant chemoradiotherapy (CRT) used to be recommended as a standard of care for locally advanced gastric cancer, this suggestion has been strongly challenged recently. However, clear evidence regarding the optimization of radiotherapy is lacking. The purpose of this study was to compare the effectiveness of preoperative CRT versus that of postoperative CRT for resectable or potentially resectable gastric cancer. Methods From January 2005 to December 2017, patients with clinical stage III/IVa (i.e., T3-4aN+M0 or T4bNxM0) locally advanced gastric cancer were retrospectively identified. Survival after preoperative CRT and postoperative CRT was assessed by unadjusted, propensity score matching (PSM) and inverse probability of treatment weight (IPTW) analyses. Moreover, exploratory subgroup analyses were performed, and toxicity and patterns of failure were also investigated. Results The median follow-up time was 32.5 months. A total of 82 and 463 patients were enrolled in the preoperative and postoperative CRT groups, respectively. After propensity score matching, preoperative CRT was associated with improved overall survival (OS) and disease-free survival (DFS) compared with postoperative CRT (3-year OS: 72.6 vs. 54.4%, log-rank p = 0.0021; 3-year DFS: 61.7 vs. 44.7%, log-rank p = 0.002). The unadjusted and IPTW analyses yielded consistent results. A complete pathologic response was achieved in 13.4% of the preoperative CRT group. Although the incidence of grade 3 or 4 adverse effects and surgical complications were similar between the two groups, significantly fewer patients experienced treatment interruptions or dose reductions due to toxic effects in the preoperative CRT setting than in the postoperative CRT setting (3.7 vs. 10.6%, p = 0.049). Conclusions Compared with postoperative CRT, preoperative CRT was associated with improved OS and DFS, superior treatment compliance and comparable surgical complications for patients with locally advanced gastric cancer. Our findings provide important evidence for the optimal combination modalities of surgery and CRT in the absence of randomized clinical data.